THE ATTRACTION AND SELECTION OF ACCOUNTING MAJORS. - Niswonger, C. Rollin (The Accounting Review, 1956)
Abstract This article presents information on the graduates entering into the field of accounting. There has been an increasing trend of business graduates, who are pursuing their majors in accounting and attracted to public accounting. It has been indicated that there had been a definite downward trend in the quality of the students in the accounting curriculum. As an additional example of this viewing with alarm, undergo the rigors of the accounting curriculum. There are undoubtedly many reasons why schools of business do not attract more of the good students. Business does not have the same prestige, as do some of the professions, notably medicine, law, and engineering. The field of business covers a broad range of activities and accommodates persons of widely varying abilities, as contrasted with the more highly specialized sciences and professions. A committee of the school of business recently made a study of the quality of their incoming students and on the basis of their findings suggested the three objectives to the faculty–to strengthen the background preparation of high school students entering college, to attract a larger percentage of the better high school students, and to give the field of business administration greater prestige in high schools.